MELAS Syndrome with Cardiac Involvement: A Multimodality Imaging Approach. (7th November 2016) - Seitun, Sara; Massobrio, Laura; Rubegni, Anna; Nesti, Claudia; Castiglione Morelli, Margherita; Boccalini, Sara; Galletto Pregliasco, Athena; Budaj, Irilda; Deferrari, Luca; Rosa, Gian Marco; Montecucco, Fabrizio; Valbusa, Alberto
Abstract : A 49-year-old man presented with chest pain, dyspnea, and lactic acidosis. Left ventricular hypertrophy and myocardial fibrosis were detected. The sequencing of mitochondrial genome (mtDNA) revealed the presence of A to G mtDNA point mutation at position 3243 (m.3243A>G) int R N A Leu(UUR) gene. Diagnosis of cardiac involvement in a patient with Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-like episodes syndrome (MELAS) was made. Due to increased risk of sudden cardiac death, cardioverter defibrillator was implanted.